How to make a game : go from idea to publication avoiding the common pitfalls along the way - Fahme, Minhaz-Us-Salakeen; Khan, Tanimul Haque (Apress, 2021)
Get a head start on making your games efficiently by avoiding common design and development pitfalls. Video games combine art and programming; this unique position has opened up opportunities for many pitfalls. This book takes you through the fundamentals of game making and the usual mistakes and bad practices that can harm your games. We start with the common difficulties and challenges, ways to find the gaps, and game design. Next, we discuss game engines and other tools you need to choose while making a game, how you should choose them, and the design documents you need to make. We also cover simple but important tweaks in game mechanics as well as the look and feel of your game. We will also discuss conventions for naming, code structuring, project structuring, and coding. Your thought process will be guided in a way that you can look for the proper approach to make a successful game. The book sheds light upon how to improve the overall game experience and finalize the game for release. Along the journey, we will explore some interesting stories of games and mythology as well. By the end of the book, you will know about the basic life cycle of a game development process and how to not make a game. You will: Discover the fundamentals of game design See some intermediate coding tricks to make your games better Grasp the pitfalls to avoid while designing and programming games Master the different conventions and practices for file naming and structuring your projects.